Effect of audit committee characteristics on company financial performance: The role of company size as a moderator - Nency Lisbeth; Mayang Sari Edastami (Journal of Innovation in Business and Economics, 2024)
This study aims to examine the effects of audit committee size, frequency of audit committee meetings, and audit committee independence on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange for the period 2017-2022. The research method employed is a quantitative descriptive approach and purposive sampling; the analysis is conducted on 170 financial statements from 34 companies. Hypothesis testing results reveal that while audit committee size does not affect financial performance, its independence has a positive impact. Company size amplifies the negative effects of audit committee size but does not influence the impact of meeting frequency or independence on financial outcomes. Overall, the audit committee plays a crucial role in ensuring the integrity of financial information and mitigating risks. The findings highlight the importance of transparency and accuracy in financial reporting and the role of the audit committee in ensuring the integrity of the information presented to the public.